Exploration of Corporate Social Responsibility Activities in Indonesia: Tourism and Creative Economy - Putri, Intan Lifinda Ayuning; Alam, Muhammad ⁠⁠⁠⁠Dimar; Rachman, Helmy Aulia (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The phenomenon of climate change is a global issue that has caught the attention of the government. The problem urges the government to enact various policies that can withstand the rate of climate change. One of the government policies is requiring companies to carry out Corporate Social Responsibility (CSR) activities. This policy has proven to increase investment in green initiatives, sustainability activities, employee training, and local community involvement. This study aims to map the CSR trends undertaken by Go Public companies in Indonesia, especially in the tourism and creative economy sector. This sector was chosen because it has a positive impact on climate change mitigation through investment in sustainable practices. The methodology used in this research is documentation to explore how the CSR of each company has evolved over several years and its trends. The findings of this study reveal the evolution of CSR from a mere philanthropic concept to a core strategy that integrates environmental sustainability, social welfare, and business growth. The implications of this research are expected to provide a more complex view of the direction of CSR development in Indonesia's tourism sector, with regards to policy, business practice, and future research.